2018
DOI: 10.1002/jper.18-0045
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokine levels and peri‐implant parameters among cigarette smokers, individuals vaping electronic cigarettes, and non‐smokers

Abstract: Background Tobacco smoking compromises the prognosis of dental implant treatment and is associated with increased risk of peri‐implant bone loss and increased implant failure rate. There is a dearth of studies that have compared clinical, radiographic, and immunological peri‐implant parameters among cigarette smokers (CS), individuals vaping e‐cigarettes (e‐cigs), and non‐smokers (NS). This study aimed to compare clinical and radiographic peri‐implant parameters and levels of matrix metalloproteinase (MMP)‐9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(113 citation statements)
references
References 40 publications
(72 reference statements)
3
110
0
Order By: Relevance
“…11 Electronic cigarettes are ENDS in which a battery is connected to a tank that contains a fluid (e-liquid) that is usually flavored and contains nicotine. 3,14 In this regard, use of ENDS is not a safe alternate to tobacco smoking. Studies 12,13 have shown that periimplant probing depth (PD), plaque index (PI), and CBL are significantly high in waterpipe smokers compared with nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Electronic cigarettes are ENDS in which a battery is connected to a tank that contains a fluid (e-liquid) that is usually flavored and contains nicotine. 3,14 In this regard, use of ENDS is not a safe alternate to tobacco smoking. Studies 12,13 have shown that periimplant probing depth (PD), plaque index (PI), and CBL are significantly high in waterpipe smokers compared with nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Although the long-term effects of vaping on health are unknown, there is mounting evidence in indexed literature that individuals using electronic cigarettes are also susceptible to periodontal and peri-implant diseases. 3,14 In this regard, use of ENDS is not a safe alternate to tobacco smoking.…”
mentioning
confidence: 99%
“…Studies [1][2][3][4] have shown that tobacco-smoking is a prospect of periodontal and peri-implant diseases, such as periodontitis and periimplantitis, respectively. Furthermore, outcomes of oral surgical interventions are undermined in tobacco smoking users compared to nonsmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Participants thought that e-cigarettes might not be damaging to crown and implants. In fact, there is an emerging body of evidence indicating that vaping not only affects oral mucosa tissues 20,11 , but also artificial oral structures, such as crown, bridges, and implants 19,21,22 . This flawed impression could be attributed to some factors: i) the general lack of reliable knowledge concerning effects of vaping; ii) some patients were attending their first appointment and may not have received reliable information about the impact vaping has on fixed prosthesis, and iii) a possible lack of standardized information provided by staff, faculty members and dental students regarding e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature has shown some effects of e-cigarettes on oral health, such as increased prevalence of three specific types of oral mucosal lesions (nicotine stomatitis, hairy tongue and angular cheilitis) among e-cigarettes users 17,18 ; and higher levels of pro-inflammatory cytokines, suggesting greater peri-implant inflammatory response 19 . In vitro studies found that e-cigarettes and other vapors devices may induce a lethal form of DNA damage that can result in chromosomal rearrangement and carcinogenesis 20 .…”
Section: Introductionmentioning
confidence: 99%